New and timely statistical indicators on government debt securities - Asier Cornejo Pérez; Jorge Diz Dias; Dagmar Hartwig Lojsch (European Central Bank (ECB), 2015)
New monthly statistical indicators on government debt securities for euro area countries have now been developed on the basis of the information contained in the Centralised Securities Database (CSDB), an internal database available to the European System of Central Banks (ESCB). The CSDB is jointly operated by the ESCB and contains timely and high-quality security-by-security reference data on debt securities, equities and investment funds. The new indicators on government debt securities provide an indication of the expected disbursements made for the servicing of issued debt securities together with the associated interest rate (nominal yield), broken down by country, original and remaining maturity, currency and type of coupon rate. This paper describes in detail the newly compiled statistical information and thus contributes to further describing the euro area government bond markets. The new indicators on euro area government debt securities are also highly relevant for policy-making and monetary and fiscal analyses. They indicate that, as at December 2014, the debt service scheduled for such securities in 2015 stood at approximately 15.9% of GDP ( exteuro1.6 trillion). This is associated with an average nominal yield on outstanding government debt securities for the euro area as a whole of 3.1% per annum. Both of these indicators have followed a decreasing path in recent periods. The new indicators also reveal some heterogeneity within the euro area: Italy shows the highest debt service and Luxembourg the lowest, while the debt securities issued by Germany have the lowest average nominal yield and Lithuanian ones the highest.
Keywords: E62; H63; H68; 330; debt securities; euro area; Government debt